Image-Guided Radiotherapy for Effective Radiotherapy Delivery - Nam Phong Nguyen (Frontiers Research Topics, 2016)
Image-guided radiotherapy (IGRT) is a new radiotherapy technology that combines the rapid dose fall off associated with intensity-modulated radiotherapy (IMRT) and daily tumor imaging allowing for high precision tumor dose delivery and effective sparing of surrounding normal organs. The new radiation technology requires close collaboration between radiologists, nuclear medicine specialists, and radiation oncologists to avoid marginal miss. Modern diagnostic imaging such as positron emission tomography (PET) scans, positron emission tomography with Computed Tomograpgy (PET-CT), and magnetic resonance imaging (MRI) allows the radiation oncologist to target the positive tumor with high accuracy. As the tumor is well visualized during radiation treatment, the margins required to avoid geographic miss can be safely reduced , thus sparing the normal organs from excessive radiation. When the tumor is located close to critical radiosensitive structures such as the spinal cord, IGRT can deliver a high dose of radiation to the tumor and simultaneously decreasing treatment toxicity, thus potentially improving cure rates and patient quality of life. During radiotherapy, tumor shrinkage and changes of normal tissues/volumes can be detected daily with IGRT. The volume changes in the target volumes and organs at risk often lead to increased radiation dose to the normal tissues and if left uncorrected may result in late complications. Adaptive radiotherapy with re-planning during the course of radiotherapy is therefore another advantage of IGRT over the conventional radiotherapy techniques. This new technology of radiotherapy delivery provides the radiation oncologist an effective tool to improve patient quality of life. In the future, radiation dose-escalation to the residual tumor may potentially improve survival rates. Because the treatment complexity, a great deal of work is required from the dosimetry staff and physicists to ensure quality of care. Preliminary clinical results with IGRT are encouraging but more prospective studies should be performed in the future to assess the effectiveness of IGRT in improving patient quality of life and local control. In this Frontiers Research Topic, we encourage submission of original papers and reviews dealing with imaging for radiotherapy planning, the physics and dosimetry associated with IGRT, as well as the clinical outcomes for cancer treatment with IGRT for all tumor sites.